Central bank policy : theory and practice - Warjiyo, Perry; Juhro, Solikin M. (Emerald Publishing, 2019)
Central Bank Policy: Theory and Practice analyses policies and practices adopted by central banks globally, as well as the institutional arrangements underlying the principles of good governance in policymaking. Discussion focuses on philosophical and conceptual theories that have key implications for central bank policy making and findings are supported by relevant quantitative analyses and case studies reflecting recent issues with respect to centralized financial policy making, including the adoption of the Inflation Targeting Framework in Indonesia. The book bridges the gap between theory and practice within the central bank policy framework by going beyond the rapidity of theoretical developments to address lesser known and understood policy practices, such as the Flexible Inflation Targeting Framework and macroprudential policy. With wide ranging scope and in-depth materials presented, alongside the authors' extensive experiences and involvement in the policymaking process at Bank Indonesia, Central Bank Policy is a vital practical tool and reference aid for policymakers, practitioners and academic researchers in the area of financial, banking, and monetary policies.